On Consept, Notion and Word - F A Kakzhanova (RUDN Journal of Language Studies, Semiotics and Semantics, 2012)
Concept, notion and word lay in the background of the deep and surface speech structures. Concepts reveal deep structure of speech, words express surface structure, notion is inherent only to minds and thought of people, which consists of concept and its code - a word, though it can also exist without any language code.